2019
DOI: 10.1002/ncp.10323
|View full text |Cite
|
Sign up to set email alerts
|

Energy Balance and Nutrition Status: A Prospective Assessment of Patients Undergoing Liver Transplantation

Abstract: Background Energy balance (EB) and its relation to nutrition status throughout the perioperative period of liver transplantation (LTx) patients has been poorly reported in the literature, and this is the primary objective of the current study. Methods A prospective observational study was conducted with patients undergoing LTx, who were assessed before and after the operation. Resting energy expenditure, total energy expenditure (TEE), dietary intake, and EB were evaluated, as well as anthropometry, handgrip s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 63 publications
(66 reference statements)
0
5
0
2
Order By: Relevance
“…Energy supply needs to be balanced towards the patients total energy expenditure (TEE), which includes REE, food-related thermogenesis and energy expenditure related to physical activity (39). A recent study of energy balance demonstrated that 77.8% of measured energy requirement was met between the 7th and 10th day after liver transplantation (183), however only 6.9% had enteral nutrition to support the energy intake. There has been a lot of debate on whether to provide a hypocaloric or isocaloric feed in ICU-patients (184).…”
Section: Energy Requirement After Liver Transplantationmentioning
confidence: 99%
“…Energy supply needs to be balanced towards the patients total energy expenditure (TEE), which includes REE, food-related thermogenesis and energy expenditure related to physical activity (39). A recent study of energy balance demonstrated that 77.8% of measured energy requirement was met between the 7th and 10th day after liver transplantation (183), however only 6.9% had enteral nutrition to support the energy intake. There has been a lot of debate on whether to provide a hypocaloric or isocaloric feed in ICU-patients (184).…”
Section: Energy Requirement After Liver Transplantationmentioning
confidence: 99%
“…Several authors have performed longitudinal follow‐up assessments of mREE in LTx patients , 8,9,24–26,50,53 for ≤50 months postsurgery (Table 3).…”
Section: Changes In Ree After Ltxmentioning
confidence: 99%
“…Studies with shorter follow‐up periods post‐LTx also revealed no changes in the mREE after surgery 50,53 . A survey of 25 liver recipients reported the mREE of patients, measured ≤72 hours post‐LTx (baseline) and at 5, 10, and 15 days postsurgery.…”
Section: Changes In Ree After Ltxmentioning
confidence: 99%
See 2 more Smart Citations